11–12-vuotiaiden lasten ringettevalmentajien käsityksiä pedagogisesta osaamisestaan ja opetustyylien käytöstä - Kemppainen, Elisa; Tiilikainen, Veera (2025)
Key words: Kemppainen, E. & Tiilikainen, V. (2024). Perceptions of pedagogical competence and teaching styles among ringette coaches of 11-12-year-old children. Faculty of Sport and Health Sciences, University of Jyväskylä, Sport Pedagogy master’s thesis, 49 p., 2 appendix.